2000
DOI: 10.1063/1.481240
|View full text |Cite
|
Sign up to set email alerts
|

Sequential addition of particles: Integral equations

Abstract: We present an integral-equation solution of the structure of systems built through the sequential quenching of particles. The theory is based on the Replica Ornstein–Zernike equations that describe the structure of equilibrium fluids within random porous matrices. The quenched particles are treated as a polydisperse system, each of them labeled by the total density at the time of its arrival. The diagrammatic expansions of the correlation functions lead to the development of the liquid-theory closures appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…In this approximation the instantaneous Replica Ornstein-Zernike (ROZ) system [3,12] reduces to a single equation determining the equilibrium configuration of the annealed molecules prior to quenching. The effect of polydispersity is included into the equation as shown in Eq.…”
Section: An Integral-equation Theory Based On Binary-mixture Approximmentioning
confidence: 99%
See 3 more Smart Citations
“…In this approximation the instantaneous Replica Ornstein-Zernike (ROZ) system [3,12] reduces to a single equation determining the equilibrium configuration of the annealed molecules prior to quenching. The effect of polydispersity is included into the equation as shown in Eq.…”
Section: An Integral-equation Theory Based On Binary-mixture Approximmentioning
confidence: 99%
“…[3] for sequential quenching is based on the multicomponent treatment, in which particles depositing on a surface at different times are regarded as different species. Its application to the RSA of the polydisperse particles was recently investigated [11].…”
Section: An Integral-equation Theory Based On Binary-mixture Approximmentioning
confidence: 99%
See 2 more Smart Citations
“…Our preliminary work 23 showed that it is actually necessary to treat the system as a mixture of an infinite number of species. The c(r) in the above equations are the direct correlation functions, i.e., the sume of all virial coefficients ͑''diagrams'' or ''cluster integrals''͒ in the corresponding total correlation functions h(r) which are free from nodal points.…”
Section: Introductionmentioning
confidence: 99%